Investigation the effect of calcination heating rate on the structural, morphological, thermal and color properties of nano Cobalt Aluminate (CoAl2O4) - Md. Farid Ahmed; Monmon Podder; Md. Rassel Moni; Md. Lutfor Rahman; Bristy Biswas; Juliya Khanam; Mahmuda Hakim; Moksodur Rahman; Md. Sahadat Hossain; Nahid Sharmin (Heliyon)
As the demand of ceramic ink is increasing rapidly for the decoration of good quality ceramic products in inkjet printing so the development of ceramic ink has become an urgent problem for ceramic industries. This study focuses on synthesizing Cobalt Aluminate (CoAl2O4), nanoparticles via sol-gel methods, utilizing different heating rate (1, 2, 3, 4, and 5°/min) during calcination. We investigate how these varying heating rates affect the properties of CoAl2O4 nanoparticles. This blue color Cobalt Aluminate is responsible for blue ceramic ink. Our findings highlight the significant impact of heating rate on shaping the characteristics of CoAl2O4 nanoparticles. Notably, increasing the heating rate triggers several noteworthy transformations. Powder X-ray diffraction (PXRD) analysis revealed sharper reflections and smaller crystallite sizes, indicative of enhanced crystallinity. The average crystallite size of the CoAl2O4 nanoparticles obtained by various peak profile analysis technique ranged 74.15–169.29 nm. Furthermore, dispersion stability in water was significantly improved with higher heating rates, a vital factor for various applications. The presence of functional groups was explored by Fourier Transform Infrared (FTIR) Spectroscopy, while Field Emission Scanning Electron Microscopy (FESEM) illustrated agglomerated nanoparticles showcasing diverse shapes. The average particle size of all the samples were measured by using ImageJ Software. These sizes ranged 73.48–39.55 nm. Energy Dispersive X-ray (EDX) Spectroscopy confirmed the purity of the composition, comprising cobalt, aluminum, and oxygen without any impurities. UV–visible spectrophotometry unraveled intriguing color changes associated with differing heating rates. As heating rates increased, a gradual shift towards less intense blue coloration (b∗ value ranged −19.77 to −17.64) was observed. The colorimetric data and the reflectivity measurement in the blue portion of the visible spectrum (400–492 nm) matched perfectly.